Applying Principles of Regenerative Medicine to Vascular Stent Development - Selvakumar, Prakash Parthiban; Rafuse, Michael Scott; Johnson, Richard; Tan, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Stents are a widely-used device to treat a variety of cardiovascular diseases. The purpose of this review is to explore the application of regenerative medicine principles into current and future stent designs. This review will cover regeneration-relevant approaches emerging in the current research landscape of stent technology. Regenerative stent technologies include surface engineering of stents with cell secretomes, cell-capture coatings, mimics of endothelial products, surface topography, endothelial growth factors or cell-adhesive peptides, as well as design of bioresorable materials for temporary stent support. These technologies are comparatively analyzed in terms of their regenerative effects, therapeutic effects and challenges faced; their benefits and risks are weighed up for suggestions about future stent developments. This review highlights two unique regenerative features of stent technologies: selective regeneration, which is to selectively grow endothelial cells on a stent but inhibit the proliferation and migration of smooth muscle cells, and stent-assisted regeneration of ischemic tissue injury.